1980
DOI: 10.1080/00140138008924804
|View full text |Cite
|
Sign up to set email alerts
|

Additional considerations concerning the effects of ‘warm’ and ‘cool’ wall colours on energy conservation

Abstract: The possibility of wall colours mediating thermal comfort was examined. Potential colour constancy problems in previous research were eliminated by painting laboratory walls either red, blue, or white. A total of 72 male and 72 female undergraduate college students were used in the study; each subject was exposed in a carrel to one of the possible combinations of the three colours and four room temperatures, 18,22,29 and 35°C. Data from forms completed by subjects under these conditions indicated that temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…They had produced, however, less spectacular results than those reported by Winett et al (1981Winett et al ( , 1982. Greene and Bell (1980) pointed out that a small number of subjects was used in these experiments, and that they were not naive. Red hues should induce a warmer feeling.…”
Section: Thermal Comfortmentioning
confidence: 77%
“…They had produced, however, less spectacular results than those reported by Winett et al (1981Winett et al ( , 1982. Greene and Bell (1980) pointed out that a small number of subjects was used in these experiments, and that they were not naive. Red hues should induce a warmer feeling.…”
Section: Thermal Comfortmentioning
confidence: 77%
“…Needless to say, the hue-heat effect is one of the multisensory phenomena between vision and thermal sensing. There have been various researches about the hue-heat effect [10][11][12][13][14][15][16][17][18][19], and we are yet to accumulated scientific knowledge about it. For example, a recent study revealed that priming a color affected thermal discrimination [20].…”
Section: Introductionmentioning
confidence: 99%
“…To date, research has been conducted to test the possible association between colour and thermal perception called hue-heat hypothesis using different ways of manipulating colour and responses types. Studies in this regard have utilized coloured lights, 2–5 coloured walls, 6 coloured cylinders, 7 and coloured googles 8 to test the hypothesis. This study investigates the impacts of correlated colour temperature (CCT) of white light on occupants’ thermal sensation and thermal comfort and examines the hue-heat hypothesis using different CCTs commonly found in the indoor workplace environment.…”
Section: Introductionmentioning
confidence: 99%